Marriage, Conflict, and Communication: Pragmatic Inquiry into Impoliteness in the Marital Relationship - Li, Shan Shan; Wu, Ying Qi (Register Journal, 2023)
The issue of impoliteness has long been a matter of interest in linguistic investigations. Considerable research has been conducted to uncover factors and features regarding the realizations of impoliteness in multiple social contexts. This study engages in a pragmatic inquiry into impoliteness in the marital relationship. The data of this study consisted of a TV episode from one famous on-site mediation reality program in China. Primarily drawing on Bousfield’s (2008) model of impoliteness realizations, this study used a qualitative approach to examine the means by which the couple in a marital relationship causes face-attacking effects and ultimately arouses conflicts. The primary findings of this study indicate that couples might struggle with various communicative challenges. A problematic marital relationship tends to be signaled in some practices of impoliteness. This study has identified thirteen realizations of impoliteness linguistically and behaviorally that indicate gender variations concerning the couple’s frequent impoliteness practices.